2013
DOI: 10.1002/bjs.9322
|View full text |Cite
|
Sign up to set email alerts
|

Altered central pain processing after pancreatic surgery for chronic pancreatitis

Abstract: After pain-relieving pancreatic surgery, patients with CP exhibit altered central pain processing compared with that in healthy controls. Poor pain outcomes are associated with more central sensitization and more pronociceptive descending pain modulation, and this should be considered when managing persistent pain after pain-relieving surgery for CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Not only can there be complications of disease including inflammation, obstruction (bile duct, pancreatic duct) as well as local complications including pseudocysts, local and central neuropathic changes also participate (2). Such neuropathic changes include central sensitization, impaired inhibitory pain modulation, as well as abnormalities of central pain processing (14-16). Given these changes, it may not be surprising then that no correlation between the imaging and pain pattern was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Not only can there be complications of disease including inflammation, obstruction (bile duct, pancreatic duct) as well as local complications including pseudocysts, local and central neuropathic changes also participate (2). Such neuropathic changes include central sensitization, impaired inhibitory pain modulation, as well as abnormalities of central pain processing (14-16). Given these changes, it may not be surprising then that no correlation between the imaging and pain pattern was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Olesen et al 66,68 explored patients with chronic pancreatitis, showing reduced CPM and central sensitization but low repeatability of CPM. Bouwense et al 7 found reduced CPM for these patients. Patients with whiplash-associated disorder had reduced CPM.…”
Section: Nociceptivementioning
confidence: 97%
“…Quantitative Sensory Testing (QST) is a validated and commonly used tool for evaluating central nociceptive processing 28. Treatment modalities that are directed at the nociceptive source (ie, the pain generator) can be expected to be less efficacious in the presence of central sensitization 29. Since no QST tests were used in this large cohort, this effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%